2001
DOI: 10.1080/095372801300107725
|View full text |Cite
|
Sign up to set email alerts
|

Understanding enterprise modelling from product modelling

Abstract: As enterprise modelling is being applied at large scale, an emerging challenge is related to managing the variety of business process models and enterprise resource models. This trend in enterprise modelling follows a similar trend in product modelling. This paper reviews to what extent themes from con-® guration management in product modelling can be positioned in enterprise modelling. The principles of progeny, view and domain, hierarchy, life cycle and variants are transferred to enterprise modelling. New i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…Enterprise architecture models mainly consider the high level view of operational interactions between enterprise processes and activities, organizational hierarchy, organizational units, system level interactions of services, information flows, enterprise strategies and goals (Wortmann et al, 2001;Morkevicius et al, 2013). For example, the perspectives (views, viewpoints) in the MODAF and NAF frameworks and UPDM are as follows: strategic view, operational view, system view, acquisition view, service view, technical view, custom viewpoint (UPDM).…”
Section: Characteristics Of Enterprise Modelling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterprise architecture models mainly consider the high level view of operational interactions between enterprise processes and activities, organizational hierarchy, organizational units, system level interactions of services, information flows, enterprise strategies and goals (Wortmann et al, 2001;Morkevicius et al, 2013). For example, the perspectives (views, viewpoints) in the MODAF and NAF frameworks and UPDM are as follows: strategic view, operational view, system view, acquisition view, service view, technical view, custom viewpoint (UPDM).…”
Section: Characteristics Of Enterprise Modelling Frameworkmentioning
confidence: 99%
“…The referred features indicate that EA frameworks are the consequence of the external paradigm. Thus, EA frameworks are mainly concerned with the high level view of interactions between enterprise processes and activities, information flows, organizational units, enterprise strategies and goals (Wortmann et al, 2001;Morkevicius et al, 2013).…”
Section: Characteristics Of Enterprise Modelling Frameworkmentioning
confidence: 99%
“…The involvement of multiple stakeholders will imply the need for different models under multiple disciplines. From this stems the architect's problem of keeping the models consistent [30].…”
Section: Engineering Domains and Architecture Descriptionsmentioning
confidence: 99%
“…These led the development of enterprise design and process design and also set the requirements for the latter. Kamaike [6] provides one example of a product categorization framework, and Wortmann et al [16] specifically compares product design and enterprise design to indicate the similarities. This is also echoed by the work of Utterback which indicated that process design follows product design which seems to make logical sense, as is depicted in Fig.…”
Section: The Evolution Of Enterprise Design As a Logical Extension Ofmentioning
confidence: 99%